Mechanistic Investigation of Au(III)‐Catalyzed Cycloisomerizations of N‐Propargylcarboxamides. Issue 40 (22nd October 2019) - Liu, Yuxia; Liu, Peng; Ling, Baoping; Chen, Guang; Chen, Tao; Li, Yulin; Bi, Siwei; Zhang, Dongju
Abstract : DFT calculations of the AuCl3 ‐catalyzed cycloisomerization of N ‐(propargyl)benzamide (1 ) have been conducted to reveal the detailed mechanism resulting in the bioactive 2, 5‐disubstituted oxazole. A viable mechanism is established, featuring the co‐catalysis of the oxazoline‐AuCl3 adduct. An oxazoline intermediate is afforded firstly by AuCl3 coordination with 1, 5‐ exo‐dig ‐cyclization, stepwise 1 ‐assisted protodeauration and coordination exchange. Once formed, the oxazoline species would replace 1 to assist the protodeauration, generating the oxazoline‐AuCl3 adduct. In the last stage, significantly different from the simple deprotonation followed by protodeauration reported previously, the exo ‐cyclic C atom of the oxazoline accepts the adjacent allyl H atom of the oxazoline‐AuCl3 to produce a zwitterionic intermediate, from which the allyl H atom of oxazoline fragment transfers to the allyl C atom of the adduct moiety, affording the final oxazole product and regenerating the oxazoline‐AuCl3 . The present theoretical study provides new insight into the mechanism of the unusual cycloisomerization reaction. Abstract : DFT calculations have been conducted to unravel the detailed mechanism of the AuCl3 ‐catalyzed cycloisomerization of N ‐(propargyl)benzamide. A novel catalytic cycle, featuring the co‐catalysis of the oxzaoline‐AuCl3 adduct, is proposed theoretically, in which the formal deprotonation followed by protodeauration is significantly different from those previously reported.